Think Aloud Pair Problem Solving (TAPPS) Strategy in Teaching Reading - Muhammad Zuhri Dj; Arman Ali (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2015)
This research is aim to know what extent the achievement of students’ reading comprehension by using Think Aloud Pair Problem Solving (TAPPS) strategy at the tenth grade students of SMKN 3 Watampone. the objectives of the research is to know what extent the achievement of student’s reading comprehension by using Think Aloud Pair Problem Solving (TAPPS) strategy. The population of this research is the tenth grade students of SMKN 3 Watampone which has 149 students. The writers applied random sampling, because the school has students more than 100 students. The X Multimedia Class is taken as the sample, because it has many students who have low values in English subject based on their teacher report. This research employs an instrument based on the problem statements investigated, It is Reading comprehension test. After several meetings, this research finds out the achievement of students’ reading comprehension significantly effective to improve the student’s reading comprehension. The result of this research shows that the mean score obtained by the students through pretest was 46.545 and posttest was 88.364; the t-test value was higher than the t-table (49.385 > 2.080). It means that there is a significant difference between the result of the students’ pretest and posttest